Forestry and forest products industries in Zambia and the role of REDD+ initiatives - Ratnasingam, Jegatheswaran; Ng'andwe, Phillimon; Ioras, Florin; Abrudan, Ioan Vasile (Commonwealth Forestry Association, 2014)
Zambia has one of the largest forest resources in southern Africa with almost 66% of its land mass under forest cover. However, indiscriminate harvesting of valuable timber resources for commodity-type products such as sawn-timber, charcoal and fuel-wood are the main drivers of forest depletion. Challenges related to customary-lands, land-tenure, lack of information about forest resources as well as the weak institutions is contributing factors that have accelerated to steady reduction of forest cover in the country. The need for investments in the forest products sector and an equitable sharing of benefits with local communities are pre-requisites to shift into higher value-added manufacturing. In the context, the implementation of the REDD+ initiatives, which aims to build capacity and technical knowledge on the ground together with improved monitoring, reporting and verifying of the forest resources data from a centrally planned command could help to arrest the depletion of the forest through better planning and management of the resources.